Dialogues in Silk: Material Explorations for Community Art Education - Lo, Jacky (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
Can silk inform us of the past, the present and a reimagined future? Jacky Lo explores this question through community art-based workshops, bringing together lost histories, family migration, and personal narratives. Lo examines weaving and embroidery to consider silk as a collaborative exchange of cultures alongside the exploration of family histories—silk’s production also represents diaspora and lost memories of Lo’s Chinese ancestry. The material of silk has been part of Chinese history and economies for centuries. In Canada, the first yard of woven silk was produced in 1922 by the Montreal-based Bruck Silk Mills at their Cowansville location. Connecting the history of silk with his own experiences, the public of Montreal are invited to create their own silk moth through the material consideration of silk and techniques of embroidery. The research confronts the inherent complexities and ethical considerations surrounding silk production. While silk is often considered a sustainable fibre, its production involves the extraction and, in many instances, the immolation of silkworms. Lo’s community gathering becomes a literal tapestry of interconnected narratives, where silk becomes not just a material but a medium for dialogue and cultural exchange. Through his workshops and research, Lo invites us to ponder the stories woven into silk, offering a glimpse into a reimagined future where the threads of the past and present converge, guided by a deeper understanding of our relationship with materials, heritage, and the self.